One‐Dimensional Covalent Organic Framework as High‐Performance Cathode Materials for Lithium‐Ion Batteries - Jia, Chao; Duan, An; Liu, Chao; Wang, Wen‐Zhuang; Gan, Shi‐Xian; Qi, Qiao‐Yan; Li, Yongjun; Huang, Xiaoyu; Zhao, Xin (Small (Weinheim an der Bergstrasse, Germany), 2023)
Covalent organic frameworks (COFs) have emerged as a new class of cathode materials for energy storage in recent years. However, they are limited to two‐dimensional (2D) or three‐dimensional (3D) framework structures. Herein, this work reports designed synthesis of a redox‐active one‐dimensional (1D) COF and its composites with 1D carbon nanotubes (CNTs) via in situ growth. Used as cathode materials for Li‐ion batteries, the 1D COF@CNT composites with unique dendritic core–shell structure can provide abundant and easily accessible redox‐active sites, which contribute to improve diffusion rate of lithium ions and the corresponding specific capacity. This synergistic structural design enables excellent electrochemical performance of the cathodes, giving rise to 95% utilization of redox‐active sites, high rate capability (81% capacity retention at 10 C), and long cycling stability (86% retention after 600 cycles at 5 C). As the first example to explore the application of 1D COFs in the field of energy storage, this study demonstrates the great potential of this novel type of linear crystalline porous polymers in battery technologies. One‐dimensional (1D) covalent organic framework (COF) has been explored as electrode materials for Li‐ion batteries. The cathodes exhibit excellent electrochemical performance, ultrahigh utilization of redox‐active sites, long cycling stability, and high rate capability. This work discloses the great application potential of 1D COF in high‐performance batteries.